(x-2)^7 + 7x(x-2)^6 = 0

The answer is x = (1/4), but I don't know how to calculate this.

Thanks.

- Dec 3rd 2012, 07:49 AMfatpsI need help solving this (already have the answer, but need the calculation)
(x-2)^7 + 7x(x-2)^6 = 0

The answer is x = (1/4), but I don't know how to calculate this.

Thanks. - Dec 3rd 2012, 08:12 AMcoolgeRe: I need help solving this (already have the answer, but need the calculation)
(x-2)^6{x-2+7x} = 0

(x-2)^6{8x-2}=0

x-2 = 0 or 8x-2 = 0

x = 2 or 8x = 2

x = 2/8 = 1/4